EFEKTIVITAS PEMBERIAN BUAH NAGA (HYLOCEREUS POLYRHIIZUS) TERHADAP KEJADIAN KONSTIPASI PADA IBU HAMIL DI POLINDES SUMBERMUJUR - Ernawati, Dwi; Widiatrilupi, Raden Maria Veronika; Safitri, Rani (NHM PRESS, 2024)
Pregnancy results in various changes in pregnant women, including mood, hormones, and physical conditions. Constipation often occurs in the third trimester of pregnancy, which can cause discomfort and health disturbances. The aim of this study is to evaluate the effectiveness of consuming dragon fruit (Hylocereus Polyrhizus) in reducing the incidence of constipation in pregnant women at the Sumbermujur Community Health Center. The research method used is a quantitative experimental design with data collection through direct observation before and after the intervention of dragon fruit. The results show that the majority of respondents were pregnant women aged 21-25 years, primipara, with an average gestational age of 34 weeks. Before the intervention, all respondents experienced constipation. However, after the intervention, 28 out of 30 respondents (93.3%) no longer experienced constipation. In conclusion, the consumption of dragon fruit is effective in reducing constipation in pregnant women at the Sumbermujur Community Health Center, providing a significant contribution to improving the health of pregnant women in rural areas. Further research is recommended to validate these findings and evaluate the long-term impact of this intervention.